The composition of the gut microbiota is altered in biliary atresia with cholangitis - Zheng, Lulu; Wu, Yibo; Gong, Zhenhua; Lv, Zhibao; Xu, Weijue; Sheng, Qingfeng; Huang, Xiong; Liu, Jiangbin (Frontiers in Surgery, 2022)
Aim To detect the composition of the gut microbiota in biliary atresia after Kasai surgery. Methods Infants within six months after the Kasai operation who were diagnosed by cholangiography at Shanghai Children’s Hospital were enrolled in the study. Fecal samples were collected from diapers, placed into sterile tubes in the inpatient department or outpatient department and frozen at −80°C within half an hour. The gut microbiota was detected by 16S rRNA sequences. Then, the patients that were followed up to one year after the Kasai operation who suffered from cholangitis at least one time were grouped into the BAcho group, and the others were grouped into the BAnoncho group. Results Nine of 18 BA patients were grouped into the BAcho group, and the others were grouped into the BAnoncho group. In the BAcho group, AST, ALT and GGT were significantly increased compared to the BAnoncho group. The number of total OTUs (operational taxonomic units) in feces was more elevated in the BAnoncho group than in the BAcho group. In the BAnoncho group, the Chao index at the OTU level was significantly increased compared to that in the BAcho group (66.37 ± 21.5 vs. 45.64 ± 11.25, p = 0.02 < 0.05). Bifidobacterium was the most abundant genus in the BAnoncho group, accounting for 22.14%, and Klebsiella accounted for 22.74% in the BAcho group. Compared with the BAnoncho group, Bacteroides was significantly decreased in the BAcho group (p = 0.037). Conclusion The composition of the gut microbiota was different between BA with cholangitis and BA without cholangitis.